Pengaruh stres kerja dan disiplin kerja terhadap produktivitas kerja karyawan PT. Handal Sukses Karya di Kabupaten Tangerang - Nur Zamzam Giovani; Aries Setiawan; Dede Saparudin; Merrisa Fermica Iskandar (Universitas Tangerang Raya, 2023)
This research aims to test and analyze the influence of work stress and work discipline on the work productivity of PT employees. Reliable Successful Work in Tangerang Regency. The method in this research uses quantitative methods. The sample used by the author in this research was 116 respondents and the sample was taken using Random Sampling Technique. The data collection method used was using a questionnaire. In this research, data analysis was carried out using SPSS version 29. Meanwhile, the data testing techniques used in this research were validity test, reliability test, normality test, homogeneity test, linearity test, multicollinearity test, multiple regression test, coefficient of determination, analysis. partial correlation and hypothesis testing (t test and f test). Based on the results of the partial correlation analysis, it can be seen that the influence value of the Job Stress and Work Discipline variables on Employee Work Productivity is 0.999 and 1.000 respectively. The results of this research show that work stress has an effect on PT employees. Reliable Successful Work. This is because the Job Stress variable has a tcount value of 3.536 > ttable of 1.980 and a significance value <0.05. Work Discipline influences the employees of PT. Handal Sukses Karya in this. This is because the Work Discipline variable has a tcount value of 4.780 > ttable 1.980 and a significance value <0.05. Work Stress and Work Discipline influence employee work productivity at PT. Handal Sukses Karya in Kab. Tangerang. This is because the Employee Work Productivity variable has an Fcount value of 15.930 > Ftable 3.08 and a significance value <0.05. The magnitude of the influence of Job Stress and Work Discipline on Employee Work Productivity is 71.4%, which means that the contribution of Employee Work Productivity can be explained by the independent variables, namely Work Stress and Work Discipline. So the remaining 28.6% is explained by other variables not examined in this study